(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
Every culture has its own traditional food practice. In the recent past, the traditional food practices and the transfer of knowledge have been in transition. A study was conducted among women tribes in Kolli Hills, Pachamalai Hills and Pechiparai in Tamilnadu to assess the Traditional Food Knowledge (TFK) of tribal women and their transmission through generations. A total number of 66 women from these three tribal and hill areas were selected randomly for this study. This study explores unique traditional food knowledge, practices and their present day adaptations and how they had used their traditional food for communicating their indigenous knowledge. A self-structured questionnaire, FGD and in-depth interviews were conducted to understand the tribe’s perception towards traditional food and communication. The results revealed that food practices in three different places were not the same and not consistent in Pachamalai. Impacts of modern food habits among the tribes were also seen in the results.